Understanding the Mechanisms of Facial Emotion Recognition in Adults with Autism Spectrum Disorders: Insights from Eye Tracking and Electroencephalography - Black, Melissa (Curtin University, 2018)
Individuals with a diagnosis of Autism Spectrum Disorder (ASD) experience significant difficulty in recognising the emotions others from facial expressions. This thesis sought to understand the attentional and neural mechanisms contributing to this difficulty in autistic adults through examining eye tracking and EEG-based outcomes during the recognition of complex, dynamic facial emotion. Cumulatively, eye tracking and EEG-based evidence suggest that altered brain functioning and visual attention may contribute to hyper-reactive responding to emotions.